2015
DOI: 10.1111/1750-3841.13111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fermentation Temperature on Key Aroma Compounds and Sensory Properties of Apple Wine

Abstract: Fermentation temperature strongly affects yeast metabolism during apple wine making and thus aromatic and quality profiles. In this study, the temperature effect during apple wine making on both the key aroma compounds and sensory properties of apple wine were investigated. The concentration of nine key aroma compounds (ethyl acetate, isobutyl acetate, isopentylacetate, ethyl caprylate, ethyl 4-hydroxybutanoate, isobutylalcohol, isopentylalcohol, 3-methylthio-1-propanol, and benzeneethanol) in apple wine signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 41 publications
(58 reference statements)
1
40
1
Order By: Relevance
“…All were inoculated at 5 ×10 6 cells/mL. The juice was fermented to dryness in demijohn at 18–20°C – appropriate for apple juice fermentation – without any assimilable nitrogen supplementation; the cider was devatted, sulphited, stored cold (3°C × 4 months) to avoid malolactic fermentation, and bottled after sterile filtration (0.45 μm). Reinette du Canada and Reinette de Champagne ciders were fermented according to the above protocol but using only the LS2 yeast strain.…”
Section: Methodsmentioning
confidence: 99%
“…All were inoculated at 5 ×10 6 cells/mL. The juice was fermented to dryness in demijohn at 18–20°C – appropriate for apple juice fermentation – without any assimilable nitrogen supplementation; the cider was devatted, sulphited, stored cold (3°C × 4 months) to avoid malolactic fermentation, and bottled after sterile filtration (0.45 μm). Reinette du Canada and Reinette de Champagne ciders were fermented according to the above protocol but using only the LS2 yeast strain.…”
Section: Methodsmentioning
confidence: 99%
“…Yeast metabolism is greatly dependent on the temperatures applied during the fermentation process. Peng et al [ 124 ] have shown that variations of the fermentation temperature have a direct influence on the aromatic profile of the final cider. In their study, the ciders fermented at 20 °C seemed to result in the best acceptance by the consumer and displayed the highest aromatic characteristics.…”
Section: Functional Improvement Of Apple Fermented Beveragesmentioning
confidence: 99%
“…This is probably due to modifications in the microbial metabolism that result in variations in the production of esters, volatile compounds and alcohols according to the fermentation temperatures. Variations in the fermentation temperature are nonetheless to be considered with care, as the increase of temperature can also lead to the formation of undesired compounds by the expression of unsuitable microbial metabolic pathways [ 124 , 125 ]. In the same way, fruit processing, pectinolytic enzyme application, cell yeast immobilization on alginate and the type of fermentation have all a significant influence on the antioxidant capacity, polyphenol profile and volatile composition of ciders [ 126 ].…”
Section: Functional Improvement Of Apple Fermented Beveragesmentioning
confidence: 99%
“…Fermentation conditions are important in winemaking, as macromolecular compounds that contribute to wine quality are extracted or synthesised during fermentation . Temperature is a parameter that affects the quality of the end‐product .…”
Section: Introductionmentioning
confidence: 99%